GLP-1 receptor agonist as an effective treatment for breast cancer-related lymphedema: a case report - Crowley, Fionnuala; Brown, Stav; Gallagher, Emily J.; Dayan, Joseph H. (Frontiers in Oncology, 2024)
Introduction: Lymphedema is a major public health issue for many women undergoing breast cancer treatment. Although weight loss has been reported to be beneficial in the treatment of lymphedema, no studies to date have examined the use of GLP-1RAs for the treatment of secondary lymphedema. This case report describes a patient who experienced significant resolution of her breast cancer-related lymphedema after initiation of a GLP-1RA for weight loss.Main symptoms and/or important clinical findings: Nine months postoperatively the patient developed arm swelling and disability. While on adjuvant chemo and hormonal therapy, her weight increased dramatically and peaked 4 years later. Corresponding to her weight gain was significant worsening of her symptoms.The main diagnoses, therapeutic interventions, and outcomes: Due to adjuvant cancerrelated weight gain and inability to lose weight with diet and exercise, she was referred for evaluation and diagnosed with lymphedema. The patient started treatment with a Glucagon-like peptide 1 receptor agonist and lost 24% of her body weight over the next 13 months. The improvement in her lymphedema mirrored her weight loss. Her limb volume difference dropped from 10.3% down to 3.4% and she no longer required a compression garment. Her imaging demonstrated return of lymphatic pumping and she experienced a significant improvement in quality of life, assessed by a validated lymphedema-specific patient reported outcome (PROM). She remains on hormonal therapy, no longer needs compression and is back to regular exercise without impairment.Conclusions: GLP-1 RAs provide a potential medical option for many patients struggling with weight gain and lymphedema. We have observed by all objective measures a significant reduction in lymphedema and the elimination of compression in the case presented as a direct result of GLP-1 RA. This may also reduce a patient's BMI to the point where they become a good candidate for lymphovenous bypass or vascularized lymph node transplant when indicated.